(−)-Epigallocatechin-3-gallate attenuates the toxicity of methylmercury in Caenorhabditis elegans by activating SKN-1. (1st July 2019) - Chen, Mo; Wang, Fan; Cao, Jing-Jing; Han, Xue; Lu, Wei-Wei; Ji, Xin; Chen, Wei-Hong; Lu, Wen-Qing; Liu, Ai-Lin
Abstract: (−)-Epigallocatechin-3-gallate (EGCG) found in tea is a natural activator of nuclear factor erythroid 2-related factor 2 (Nrf2), a primary regulator of the cellular defense system. The adverse health effects resulting from methylmercury (MeHg) exposure in humans are of worldwide concern. We hypothesized that EGCG could induce a Nrf2-mediated protective response to antagonize MeHg toxicity. Using the Caenorhabditis elegans ( C. elegans ) nematode model, we observed that EGCG activated SKN-1 (the functional ortholog of Nrf2 in C. elegans ), as shown by the increased skn- 1 mRNA level, induction of the gene gst-4, and enhanced SKN-1-mediated oxidative stress resistance that were indicated by elevation of total antioxidant ability and reductions in reactive oxygen species and malondialdehyde. Following exposure to MeHg, EGCG-treated C. elegans displayed increased survival rates, improved locomotion behaviors, decreased numbers of damaged neurons, and reduced oxidative damage compared to the controls. Moreover, the protective effects of EGCG against MeHg toxicity were counteracted by RNA-mediated interference of skn-1 . These results demonstrated that EGCG could alleviate MeHg toxicity by upregulating the SKN-1-regulated protective response in C. elegans . Our study suggests a potentially beneficial effect of targeting Nrf2 by dietary EGCG in protecting humans against MeHg toxicity. Highlights: Activating SKN-1 by EGCG confers resistance to oxidative stress in C. elegans. EGCG protects C. elegans from MeHg toxicity via SKN-1. Dietary EGCG may be helpful to prevent potential human MeHg exposure hazards. Dietary strategy targeting Nrf2 against environmental insults is attractive.